Transmanubrial Approach for Removing a Head and Neck Tumor Located at the Upper Lateral Mediastinum - Masuda, Muneyuki (Biomed Hub, 2017)
BACKGROUND: When a head and neck tumor invades the upper lateral mediastinum, the transmanubrial approach (TMA), in which the sternoclavicular joint is temporary mobilized and replaced back to the physiological position, appears to be an excellent method. However, there have been only a few reports about the application of this approach to head and neck tumors. MATERIALS AND METHODS: We recently adopted this technique for the removal of 2 head and neck tumors that required handling of the subclavian and innominate veins around the venus angle. RESULTS: We could safely remove the tumors under good surgical view and obtained excellent cosmetic and functional results. CONCLUSIONS: TMA is a useful technique for the removal of head and neck tumors, which invade the upper lateral mediastinum. More frequent applications of this method are encouraged in combination with head and neck tumor surgery.